(untitled) (Herald of the National Children’s Medical Center, 2025)
Aim. To systematize current data on the potential of ultrasound assessment of hemodynamic parameters in preterm infants, with a focus on the use of cerebral Doppler and targeted neonatal echocardiography (TNE) for the early detection of critical conditions. Materials and methods. A review was conducted of publications in peer-reviewed journals from 2018 to 2025, including systematic reviews, clinical guidelines, and original studies addressing the assessment of cerebral blood flow (parameters RI, PI, PSV) and functional echocardiography for the diagnosis of cardiovascular instability. The analysis included data on the application of innovative technologies such as NeoDoppler and protocols for dynamic ultrasound monitoring in neonatal intensive care units. Results. The summarized evidence confirms the high prognostic value of cerebral Doppler in detecting the risk of ischemic and hemorrhagic brain injuries, as well as the effectiveness of TNE for assessing cardiac output, pulmonary hypertension, and patent ductus arteriosus. Integrating these methods enables the creation of a comprehensive model for hemodynamic monitoring in preterm infants. Conclusion. Ultrasound assessment of hemodynamic parameters, including cerebral Doppler and targeted echocardiography, is a promising tool for the early prediction and prevention of life-threatening conditions in preterm infants. Further clinical studies are needed to standardize normal parameter values, develop unified protocols, and integrate innovative technologies into routine neonatal intensive care practice.